"Sinologism": Rethinking the Legitimacy of Sinology as Knowledge. Issue 1 (2nd January 2018) - Zhou, Ning
Editors' Abstract: This article starts with a question on the nature and function of Sinological studies and casts doubts on the legitimacy of Sinology as a pure and objective branch of learning. After briefly reviewing the rise of Sinology as a branch of knowledge, it conducts a critical analysis of its major premises and orientations. Subjecting them to a scrutiny in terms of postmodern and postcolonial theories of knowledge production, it draws the conclusion that Sinology differs from Oriental studies only in degree, but not in kind. Recognizing the complexity of the field, the article nevertheless suggests that in the final analysis, Western Sinology comes more closely to a narrative, a type of discourse, which produces knowledge of China not entirely on objective reality, but with cultural and ideological imaginations.